Impact of a Safety Huddle–Based Intervention on Monitor Alarm Rates in Low‐Acuity Pediatric Intensive Care Unit Patients. Issue 8 (1st August 2017) - Dewan, Maya; Wolfe, Heather; Lin, Richard; Ware, Eileen; Weiss, Michelle; Song, Lihai; MacMurchy, Matthew; Davis, Daniela; MSCE, Christopher P. Bonafide MD
Abstract : BACKGROUND: Physiologic monitors generate high rates of alarms in the pediatric intensive care unit (PICU), yet few are actionable. OBJECTIVE: To determine the association between a huddle‐based intervention focused on reducing unnecessary alarms and the change in individual patients' alarm rates in the 24 hours after huddles. DESIGN: Quasi‐experimental study with concurrent and historical controls. SETTING: A 55‐bed PICU. PARTICIPANTS: Three hundred low‐acuity patients with more than 40 alarms during the 4 hours preceding a safety huddle in the PICU between April 1, 2015, and October 31, 2015. INTERVENTION: Structured safety huddle review and discussion of alarm causes and possible monitor parameter adjustments to reduce unnecessary alarms. MAIN MEASUREMENTS: Rate of priority alarms per 24 hours occurring for intervention patients as compared with concurrent and historical controls. Balancing measures included unexpected changes in patient acuity and code blue events. RESULTS: Clinicians adjusted alarm parameters in the 5 hours following the huddles in 42% of intervention patients compared with 24% of control patients ( P = .002). The estimate of the effect of the intervention adjusted for age and sex compared with concurrent controls was a reduction of 116 priority alarms (95% confidence interval, 37‐194) per 24 hours ( P = .004). There were no unexpected changes in patient acuity or code blue events related to the intervention. CONCLUSION: Integrating a data‐driven monitor alarm discussion into safety huddles was a safe and effective approach to reducing alarms in low‐acuity, high‐alarm PICU patients.